Proving Two Partition Identities - da Silva, Robson; Filho, Jair Cunha; Santos, José Plínio Oliveira (Trends in Computational and Applied Mathematics, 2012)
In this paper we give combinatorial proofs for two partition identities. The first one solves a recent open question formulated by G. E. Andrews.